Pyrolysis characteristics and kinetics of human faeces, simulant faeces and wood biomass by thermogravimetry–gas chromatography–mass spectrometry methods. (November 2020) - Somorin, Tosin; Parker, Alison; McAdam, Ewan; Williams, Leon; Tyrrel, Sean; Kolios, Athanasios; Jiang, Ying
Abstract: Human faeces (HF) are treated as wastes in many parts of the world, a resource that can be converted to energy and fuels. To enhance the understanding of fuel conversion processes and decomposition characteristics, this study investigated the pyrolysis behaviour and evolved gas profiles of HF using thermogravimetry with gas chromatography–mass spectrometry methods. Kinetic parameters were deduced using model-free kinetic models. Results are compared with simulant faeces (SF), wood biomass (WB) and HF–WB blends. The pyrolysis of HF involved two decomposition peaks — a fronting peak with weight loss of ∼ 51 wt% and a tailing shoulder peak with weight loss of ∼ 15 wt%. The apparent activation energy for HF varied from 122–382 kJ/mol at conversion rates of 10%–90% using Kissinger–Akahira–Sunose model. Some of the key pyrolysis products for HF at 370 °C were 4-methoxy-phenol, n-hexadecanoic acid, phenol, 4-methyl- and indole isomer (pyrrolo[1, 2-a]pyridine). At 530 °C, evolved gases were largely fragmented with high proportions of alkanes and alkenes including 3-dodecane, 2-undecane, 6-tridecene, 2-propenylidene-cyclobutene. These products differed to WB that are largely hydroxyphenyls and methoxyphenols with guaiacyl or syringil structures. Blending with WB improved pyrolysis of HF, irrespective of the proportions of blend.